A Polysulfide‐Immobilizing Polymer Retards the Shuttling of Polysulfide Intermediates in Lithium–Sulfur Batteries. Issue 45 (25th September 2018) - Tu, Shuibin; Chen, Xiang; Zhao, Xinxin; Cheng, Mingren; Xiong, Peixun; He, Yongwu; Zhang, Qiang; Xu, Yunhua
Abstract: Lithium–sulfur batteries are regarded as one of the most promising candidates for next‐generation rechargeable batteries. However, the practical application of lithium–sulfur (Li–S) batteries is seriously impeded by the notorious shuttling of soluble polysulfide intermediates, inducing a low utilization of active materials, severe self‐discharge, and thus a poor cycling life, which is particularly severe in high‐sulfur‐loading cathodes. Herein, a polysulfide‐immobilizing polymer is reported to address the shuttling issues. A natural polymer of Gum Arabic (GA) with precise oxygen‐containing functional groups that can induce a strong binding interaction toward lithium polysulfides is deposited onto a conductive support of a carbon nanofiber (CNF) film as a polysulfide shielding interlayer. The as‐obtained CNF–GA composite interlayer can achieve an outstanding performance of a high specific capacity of 880 mA h g −1 and a maintained specific capacity of 827 mA h g −1 after 250 cycles under a sulfur loading of 1.1 mg cm −2 . More importantly, high reversible areal capacities of 4.77 and 10.8 mA h cm −2 can be obtained at high sulfur loadings of 6 and even 12 mg cm −2, respectively. The results offer a facile and promising approach to develop viable lithium–sulfur batteries with high sulfur loading and high reversible capacities. Abstract : A polysulfide‐immobilizing polymer shield is designed by depositing a natural polymer of Gum Arabic (GA) onto high‐conductivity carbon nanofiber (CNF) films as interlayers of Li–S batteries, which not only provides a large active surface and strong chemisorption for immobilizing soluble polysulfides but also ensures a good contact between the CNFs and GA, thus effectively reusing the adsorbed active materials.